Object-Oriented Programming with Smalltalk - Wertz, Harald (ISTE Press Limited - Elsevier Incorporated, 2015)
Object oriented programming is a way of thinking about problems.Smalltalk is one of the purest incarnations of an object-oriented programming language.Using a pedagogical approach, this book covers all aspects of object oriented programming: first through the study of various preexisting Smalltalk classes, their implementation and use; then.